Physio Mechanical, Thermal And Biodegradation Studies Of Paddy Straw Powder Filled Polylactic Acid And Poly 3 Hydroxybutyrate- Co-3- Hydroxyvalerate Biocomposites - Yaacob, Noorulnajwa Diyana (2017)
Environmental problems associated with the use of synthetic polymers have resulted to the utilization of biodegradable polymer and natural fiber for producing fully biodegradable composite. This study has been carried out to produce such composites with the use of paddy straw powder (PSP) in the poly lactic acid (PLA) or poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). In this study, the effect of filler loading, treatment of natural filler and blending of two biopolymers on the mechanical, physical, thermal and biodegradability properties of composites were studied. Firstly, the PLA/PSP and PHBV/PSP composites containing 0-20 wt. % of PSP were prepared by using melt-blended mixing and compression molding method. The addition of PSP had resulted in reduced tensile strength for both of composites. The addition of PSP also showed reduction in thermal stability and has boosted up the water absorption percentages due to their hydrophilic nature. The tensile properties, FTIR, SEM and weight loss of soil buried samples proved the degradation activities over the predetermined time. In terms of comparison tensile strength of PHBV/PSP composites were lower than that of PLA/PSP composites. Thermal stability was also reduced but much lower as compared to PLA/PSP composites. After that the effect of chemical modification of PSP using acrylic acid (AA) and NaOH were studied on the mechanical properties, morphology and thermal properties of PLA/PSP composites. The treated composites with AA and NaOH have higher tensile properties compared to untreated composites. The chemical modification enhanced the thermal stability of treated composites. The FTIR analysis showed that chemical modification of PSP has reduced the hydroxyl group of PSP. The better interfacial interaction between PSP and PLA was proof by SEM. As compared both of the two types chemical modification, acrylic acid showed a good properties as compared to the sodium hydroxide. Furthermore, blending of two biopolymers which were PLA and PHBV was done in the ratio of 50:50. The PLA/PHBV blends were reinforced with the AA-treated PSP and the mechanical, thermal morphology and water absorption were studied. The tensile strength of the PLA/PHBV blends were slightly lower as compared to the pure PLA. The addition of the AA-treated PSP resulted in reduced tensile strength. As compared to the the PLA/PSP (AA-treated), the PLA/PHBV/PSP composites showed slightly lower tensile properties, thermal stability and water absorption. This may attributed to the relatively weak polymer-polymer interfaces and immiscibility between PLA and PHBV. Lastly, the fungal flora decomposing PLA/PSP and PHBV/PSP composites were investigated from the soil buried of these composites using streak plate method. 5 strains were isolated which are 3 strains from the PLA/PSP composites (PLA1, PLA2, PLA3) and 2 strains from PHBV/PSP composites PHBV1 and PHBV2). 18s sequencing method was applied in order to identify the species of the microorganisms. Based on the results, only two types of fungi, namely the Aspergillus fumigatus and Trichoderma harzianum were able to degrade the PLA/PSP composite, while for the PHBVB/PSP composite, two types of fungi also, namely the Aspergillus fumigatus and Aspergillus niveus, were involved.